The Divorce Causes of Couples with 30 Years Marriage Period or More in the View of Judges at Mojokerto Religious Court - Ermawan, Mohamad Zakky Ubaid (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
For couples who have lived together for more than 30 years, feeling sad and happy together, and accepting weaknesses of each partner, are their habit in daily life. However, if they chose to divorce, this is a very unfortunate thing. In this thesis, the research questions are (1) What are the factors causing divorce of couples with 30 years marriage period or more in the view of judges at Mojokerto Religious Court? And (2) what are the judges’ considerations in judging divorce of couples with 30 years marriage period or more? The type of research used in this thesis is a field research and the approach is a qualitative approach. The author uses two methods of data collecting those are interview and documentation. In result, the judges’ say there are some divorce causes according to this matter, those are (1) financial problems, (2) infidelity, (3) boredom, (4) irresponsibility of their children, (5) emotionally disconnected, (6) failure of the husband to lead his family, (7) domestic violence, (8) major changes in priorities, (9) And unresolved conflict. None become their prime consideration, and nothing taken into account in judging this type of divorce case unless the facts and the proof which the spouses brought.